COMPARATIVE STUDY BETWEEN SASAKNESE AND ENGLISH AFFIXATION TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Nafisah, Baiq Zuhrotun; Sugianto, Sugianto; Suadiyatno, Taufik (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2018)
The research is aimed at finding out the distinctive between Sasak language and English language affixation in which this is the starting point of investigating whether or not it has some similarities or may differences. The similarities will bring the easiness to the students while the differences will bring the difficulties. The result of the study is very particularly aimed to improve students’ vocabulary mastery during the classroom teaching action. Hopefully, it will bring some positive effect on students’ mastery regarding to the worse condition of vocabulary mastery. The interview was conducted closely to the research participants to dig up the information on how the affixation might change the meaning of particular word in Sasak language which then confirmed to that of English language have. The data collected through the interview process then will be transcribe and reduced based on research need for the sake of answering the research question. The research conclusion was made based on data finding during the field interview process. The research result than applied in the classroom teaching practice and published widely on journal of English language teaching.